How Results of The Ability to Understand Physics on Newton's Motion Law Material using Guided Inquiry? - Ma'ruf Ma'ruf; Novita Maumude; Khaeruddin Khaeruddin (Kasuari: Physics Education Journal (KPEJ), 2020)
The main problem in this research is how the results of the level of understanding of physics concepts on the aspect of translation through the guided incuri learning model? The type of this research is True Experimental Design by using Posttest-Only Control Design. The research instrument used was a test of understanding the concept of the translational aspects of physics in the form of essay questions. The population is 120 students from class X of SMKN Buyasuri, and the sample is X class students "Ruminansia" totaling 30 people and "Poultry" totaling 30 people. The analysis technique used is descriptive analysis and inferential analysis through normality test, homogeneity test, and hypothesis testing. The results of descriptive statistical analysis showed that the level of understanding the concept of the physics translation aspects of class X students in Ruminansia that were taught using the guided inquiry model obtained an average score of 85.33 and a standard deviation of 7.63 and an understanding of the concept of the physics translation aspects of Poultry class students taught without using the guided inquiry model obtained an average score of 70.33 and a standard deviation of 9.90. While the results of inferential statistical analysis show that the two classes come from homogeneous normally distributed populations and the value of tcount> ttable is 6.474> 1.673.